Organocatalyzed [2+2] Cycloaddition Reactions between Quinone Imine Ketals and Allenoates - Liu, Teng; He, Chixian; Wang, Fan; Shen, Xiang; Li, Yongqin; Lang, Man; Li, Guijun; Huang, Chao; Cheng, Feixiang (Synthesis, 2020)
A new cycloaddition reaction of quinone imine ketals (QIKs), which could be utilized to the construction of functionalized azaspirocyclics under mild conditions, is described. This transformation involved a [2+2] cycloaddition reaction between QIKs and allenoates catalyzed by DABCO, and then treatment with 1 N HCl in one-pot. The strategy could provide a practical route to access azetidine-fused spirohexadienones in good to excellent yields and with high E-selectivity.
Keywords: quinone imine ketals; allenoates; [2+2] cycloaddition; E-selectivity